Novel mitoviruses in Rhizoctonia solani AG-3PT infecting potato. Issue 3 (March 2016) - Das, Subha; Falloon, Richard E.; Stewart, Alison; Pitman, Andrew R.
Abstract: Double-stranded RNA (dsRNA) elements are ubiquitous in Rhizoctonia solani . Total dsRNA was randomly amplified from a R. solani isolate (RS002) belonging to anastomosis group-3PT (AG-3PT), associated with black scurf in potato. Assembly of resulting cDNA sequences identified a nearly complete genome of a novel virus related to the genus Mitovirus (family Narnaviridae ), herein named Rhizoctonia mitovirus 1 RS002 (RMV-1-RS002). The 2797 nucleotide partial genome of RMV-1-RS002 is A-U rich (59.06 %), and can be folded into stable stem-loop structures at 5′ and 3′ ends. Universal and mold mitochondrial codon usages revealed a large open reading frame in the genome, putatively encoding an 826 amino acid polypeptide, which has conserved motifs for mitoviral RNA-dependent RNA polymerase. The full length putative polypeptide shared 25.6 % sequence identity with the corresponding region of Tuber excavatum mitovirus (TeMV). The partial genome of a second mitovirus (proposed name Rhizoctonia mitovirus 2 RS002 (RMV-2-RS002)) was also amplified from RS002. A nearly identical copy of RMV-1-RS002 was detected in two additional AG-3PT isolates. These data indicate that multiple mitoviruses can exist in a single isolate of R. solani AG-3PT, and that mitoviruses such as RMV-1-RS002 are probably widespread in this pathogen. The roles of mitoviruses in the biology of R. solani AG-3PT remain unknown.